Integrated Reporting and the Directions of Its Development - Krasodomska, Joanna (Olsztyn Economic Journal, 2014)
The aim of the paper is to present the concept of integrated reporting. Its aim is to explain to the stakeholders how value is created by a company with the use of its resources and relations as well as interactions with the external environment. The integrated reporting framework has been developed by the International Integrated Reporting Council, and the reason for this was the economic crisis. It seems that in view of the limitations of traditional financial accounting, it is advisable for companies to start practicing integrated reporting. This issue is also worth addressing within contemporary accounting research.